Aftershocks first story ; Aftershocks : second story ; Aftershocks : third story [videorecording] - Lazaro, Cheche; Quiano, Kathy; Ramos, Angie; Ressa, Maria (The Probe Team, 1990)
A three part series on the July 16, 1990 earthquake that rocked Luzon. With epicenter in Cabanatuan City, it measured 7.7 on the Richter scale. The first deals with stories from survivors of the quake. The second talks about the safety of structures and our disaster preparedness. The third deals with the economic effects of the quake on the market goods.